Analisis Faktor Konsumen Pria Membeli Jasa Perawatan Wajah di Larissa Aesthetic Center Semarang - Vany Dwi Hapsari; M. Widyanto (Universitas Katolik Soegijapranata, Semarang, 2019)
This research was conducted to know the reasons male consumers buy face treatment. Survey was conducted and sampling by purposive sampling toward 105 respondents and collecting data by questionnaires. The results of factor analysis by SPSS software showed 6 factors identified which influenced male consumer tend buying face treatment in Larissa Aesthetic Center Semarang. First factor was expert doctor and price promotion (variance 29.4%). Second factor was accessability (variance 14.2 %). Third factor was service quality (variance 11.3%). Fourth factor was membership card (variance 6.2%). Fifth factor was quality and parking space (variance 5.4%). And sixth factor was service and consumer testimony (variance 4.9%).